The evaluation of the positioning accuracy of the EGNOS and DGPS systems based on the long-term measurements in the years 2006–2014 - Specht Mariusz (Polish Cartographical Review, 2015)
The DGPS (Differential GPS) and EGNOS (European Geostationary Navigation Overlay Service) systems belong to a group of systems supporting the global satellite system GPS (Global Positioning System). These systems have significantly better navigation performance than GPS and, therefore, they are widely used in the maritime, civil and air navigation. The analysis of the positioning accuracy of GPS leads to the conclusion: from year to year the accuracy of the positioning determination increases. The effect of the permanent increasing of the GPS positioning accuracy is the parallel increasing of the positioning accuracies of all the supporting systems. In connection with the constant improvement of the precision characteristics of the above mentioned systems on one hand and the fact, that the users do not possess the current information about the actual status of these characteristics on the other hand, it is reasonable to conduct the periodical research in this area. For that purpose the long-term measurement campaigns were realized in the years 2006-2014; the values of measures, describing the positioning accuracies obtained by both systems, were determined on the basis of those campaigns.